The basics of performance measurement - Harbour, Jerry L. (CRC Press, 2009)
The Basics of Performance Measurement helped pioneer the science of performance measurement. This little yellow book provides a five-step method that shows how to design performance measurement families and how to build hierarchies tailored to different levels within an organization.